2020
DOI: 10.1515/cclm-2020-0566
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxic effects and myocardial injury: the search for a more precise definition of drug cardiotoxicity

Abstract: Drug-induced cardiotoxicity is a major clinical problem; cardiotoxic drugs may induce both cardiac dysfunction and myocardial injury. Several recent studies reported that cardiac troponins measured with high-sensitivity methods (hs-cTn) can enable the early detection of myocardial injury related to chemotherapy or abuse of drugs that are potentially cardiotoxic. Several authors have some concerns about the standard definition of cardiotoxicity, in particular, regarding the early evaluation of chemotherapy card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Other mechanisms of troponin release, in the absence of a myocardial damage, are normal myocardial cell turnover and cell release of cTn breakdown products (Figure 2). However, it is not clinically possible to distinguish the mechanisms that cause the cTn level to rise from the laboratory result alone [11][12][13][14].…”
Section: Main Phatophysiological Mechanism Pathologymentioning
confidence: 99%
“…Other mechanisms of troponin release, in the absence of a myocardial damage, are normal myocardial cell turnover and cell release of cTn breakdown products (Figure 2). However, it is not clinically possible to distinguish the mechanisms that cause the cTn level to rise from the laboratory result alone [11][12][13][14].…”
Section: Main Phatophysiological Mechanism Pathologymentioning
confidence: 99%
“…Because acute myocardial infarction due to myocyte ischaemia and hypoxia could lead to myocardial cell necrosis and destruction of cell membranes and organelles, the release of troponin into the bloodstream can be detected. Possible pathophysiological causes of troponin elevation in patients with CTRCD include 30 excitation/contraction coupling and/or alterations in intracellular calcium homeostasis and/or mitochondrial function, leading to cardiomyocyte dysfunction; altered cardiac pre‐loading and post‐loading conditions; and alterations in extracellular matrix composition 31,32 . The injury in CTRCD begins at the cellular level before abnormal cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Possible pathophysiological causes of troponin elevation in patients with CTRCD include 30 excitation/contraction coupling and/or alterations in intracellular calcium homeostasis and/or mitochondrial function, leading to cardiomyocyte dysfunction; altered cardiac pre-loading and post-loading conditions; and alterations in extracellular matrix composition. 31,32 The injury in CTRCD begins at the cellular level before abnormal cardiac func- tion. The ability of hs-cTnT to accurately identify small changes in troponin concentration (increase or decrease) within a short time period provides greater analytical accuracy and clinical sensitivity for acute myocardial injury and, thus, allows identification of early myocardial injury at the cellular level.…”
Section: P P 2176mentioning
confidence: 99%
“…In addition, including biomarkers in the algorithms of CTRCD detection allows for a comprehensive evaluation of cardiac function. Studies have shown that elevated levels of the primary cardiac biomarkers, troponin and B-type natriuretic peptide, are significantly associated with HF and asymptomatic LVD within cancer treatment [18][19][20][21][22][23]. Several new potential biomarkers, such as C-reactive protein (CRP), soluble suppression of tumorigenicity 2 (sST2), galectin-3 (Gal-3), myeloperoxidase (MPO), placental growth factor (PIGF), tumor growth differentiation factor (GDF-15), and microRNAs, hold promise for predicting cardiovascular disease not only in cancer patients but in cases of other chronic diseases [24,25].…”
Section: Introductionmentioning
confidence: 99%